La prison est-elle obsolète ? - Davis, Angela; Peronny, Nathalie (Au diable vauvert, 2014)
"Comment et pourquoi plus de deux millions d’américains sont aujourd’hui derrière les barreaux ? Comment les entreprises font-elles profit du système carcéral ? Quels sont les mécanismes qui conduisent à criminaliser les communautés de couleur et à désaffilier politiquement de larges franges d’électeurs dans les minorités ? Comment et pourquoi plus de deux millions d'américains vivent en prison ? Comment les entreprises font-elles profit du système carcéral ? Quels sont les mécanismes qui criminalisent les communautés de couleur et désaffilient politiquement les électeurs des minorités ?
Keywords: afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; capitalisme; cours; discipline; droits civiques; esclavagisme; féminismes noirs; histoire et politique; inégalités; justice sociale; militance; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Duke University Press, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Section: x, 219 p. : ill. ; 23 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles